MXene-Derived Defect-Rich TiO2@rGO as High-Rate Anodes for Full Na Ion Batteries and Capacitors - Fang, Yongzheng; Zhang, Yingying; Miao, Chenxu; Zhu, Kai; Chen, Yong; Du, Fei; Yin, Jinling; Ye, Ke; Cheng, Kui; Yan, Jun; Wang, Guiling; Cao, Dianxue (Nano-Micro Letters, 2020)
Sodium ion batteries and capacitors have demonstrated their potential applications for next-generation low-cost energy storage devices. These devices's rate ability is determined by the fast sodium ion storage behavior in electrode materials. Herein, a defective TiO2@reduced graphene oxide (M-TiO2@rGO) self-supporting foam electrode is constructed via a facile MXene decomposition and graphene oxide self-assembling process. The employment of the MXene parent phase exhibits distinctive advantages, enabling defect engineering, nanoengineering, and fluorine-doped metal oxides. As a result, the M-TiO2@rGO electrode shows a pseudocapacitance-dominated hybrid sodium storage mechanism. The pseudocapacitance-dominated process leads to high capacity, remarkable rate ability, and superior cycling performance. Significantly, an M-TiO2@rGO//Na3V2(PO4)3 sodium full cell and an M-TiO2@rGO//HPAC sodium ion capacitor are fabricated to demonstrate the promising application of M-TiO2@rGO. The sodium ion battery presents a capacity of 177.1 mAh g−1 at 500 mA g−1 and capacity retention of 74% after 200 cycles. The sodium ion capacitor delivers a maximum energy density of 101.2 Wh kg−1 and a maximum power density of 10,103.7 W kg−1. At 1.0 A g−1, it displays an energy retention of 84.7% after 10,000 cycles. Highlights: 1 A freestanding MXene-derived defect-rich TiO2@reduced graphene oxides (M-TiO2@rGO) foam electrode was fabricated. 2 M-TiO2@rGO presents fast Na+ storage kinetics due to capacitive contribution. 3 M-TiO2@rGO foam electrode displays a capacity retention of 90.7% after 5000 cycles.